Laser speckle contrast imaging to monitor microcirculation: An effective method to predict outcome in patients with sepsis and septic shock - Ruan, Zhengshang; Li, Ran; Dong, Wenwen; Cui, Zhilei; Yang, Hui; Ren, Rongrong (Frontiers in Bioengineering and Biotechnology, 2023)
Background: This study examines the microcirculation of patients with sepsis and septic shock using Laser Speckle Contrast Imaging (LSCI) technology, to enhance monitoring and predict outcomes of sepsis and septic shock. Methods: From July 01, 2021, to January 31, 2022, 44 patients diagnosed with septic shock and sepsis were included in the study, their clinical data were collected, and LSCI was used to monitor the mean peripheral blood flow perfusion index (PI). Results: The average peripheral blood flow PI of septic shock patients was significantly lower than that of septic patients, with a cutoff value of 26.25. The average peripheral blood flow PI negatively correlated with acute physiology and chronic health evaluation (APACHE) Ⅱ score (P = 0.01< 0.05), sequential organ failure assessment (SOFA) score (P < 0.01), and lactic acid levels (P = 0.01< 0.05). We report average peripheral blood flow PI correlation with age, mean arterial pressure, body temperature, oxygen saturation, heart rate, and body mass index. There was no correlation with procalcitonin, cold reactive protein C-reactive protein (CRP), red blood cell distribution width, or platelet distribution width (P > 0.05). PI significantly correlated with the outcome or mortality (P < 0.001, r = -0.865). The ROC curve was calculated for PI and the sensitivity was 81.3 %, the specificity was 75% when PI cutoff value choose 20.88. Conclusion: LSCI technology successfully detected the fingertip microcirculation of patients with septic shock. LSCI can reliably differentiate patients with sepsis vs. patients with septic shock. Additionally, the average peripheral blood PI negatively correlated with APACHE Ⅱ, SOFA score and lactate acid levels, providing useful and supplementary information for the diagnosis and monitoring of septic shock.